Sorting Nexin 27 Enables MTOC and Secretory Machinery Translocation to the Immune Synapse - González-Mancha, Natalia; Rodríguez-Rodríguez, Cristina; Alcover, Andrés; Merida, Isabel (Frontiers in Immunology, 2022)
Sorting nexin 27 (SNX27) association to the retromer complex mediates intracellular trafficking of cargoes containing PSD95/Dlg1/ZO-1 (PDZ)-binding C-terminal sequences from endosomes to the cell surface, preventing their lysosomal degradation. Antigen recognition by T lymphocyte leads to the formation of a highly organized structure named the immune synapse (IS), which ensures cell-cell communication and sustained T cell activation. At the neuronal synapse, SNX27 recycles PDZ-binding receptors and its defective expression is associated with synaptic dysfunction and cognitive impairment. In T lymphocytes, SNX27 was found localized at recycling endosomal compartments that polarized to the IS, suggesting a function in polarized traffic to this structure. Proteomic analysis of PDZ-SNX27 interactors during IS formation identify proteins with known functions in cytoskeletal reorganization and lipid regulation, such as diacylglycerol (DAG) kinase (DGK) ζ,,as well as components of the retromer and WASH complex. In this study, we investigated the consequences of SNX27 deficiency in cytoskeletal reorganization during IS formation. Our analyses demonstrate that SNX27 controls the polarization towards the cell-cell interface of the PDZ-interacting cargoes DGK and the retromer subunit vacuolar protein sorting protein 26, among others. SNX27 silencing abolishes the formation of a DAG gradient at the IS and prevents re-localization of the dynactin complex component dynactin-1/ p150Glued, two events that correlate with impaired microtubule organizing center translocation (MTOC). SNX27 silenced cells show marked alteration in cytoskeleton organization including a failure in the organization of the microtubule network and defects in actin clearance at the IS. Reduced SNX27 expression was also found to hinder the arrangement of signaling microclusters at the IS, as well as the polarization of the secretory machinery towards the antigen presenting cells. Our results broaden the knowledge of SNX27 function in T lymphocytes by showing a function in modulating IS organization through regulated trafficking of cargoes.